(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
According to the World Health Organization (WHO), the number of people with physical and mental disabilities in the world has reached more than 1 billion people, these are people with disabilities for various reasons, which is 15% of the population. WHO believes that basic rehabilitation services can improve the health of 1.5% of the population in developing countries. These are mainly people with limited mobility, vision, hearing and learning difficulties. The problem of rehabilitation is one of the 43 scientific programs being developed within WHO. Within the framework of this program, cooperation with 30 international non-governmental organizations was carried out.